Lacto S.A. – caso práctico - Bazan Rodriguez, Andrea Stefanny (2019)
The present work of professional sufficiency has as its main objective the analysis of the Financial Statements along with the measurement of the effects generated by the implementation of the International Financial Reporting Standards applied since 2018 in the company Lacto SA, the objective is to establish the company value for a possible purchase option. Based in the information of the 2017 and 2018 period, it has been used as a basis for analysis and to make the projection of the following 12 years. This has allowed the evaluation of the economic impacts on the company and a better decision making at the corporate level. To carry out the projection of the impacts on the application of IFRS, information has been collected through various sources, including: Consolidated Financial Statements of Gloria SA, Separate Financial Statements of Laive SA, Valuation thesis of various universities entities, Lima Stock Exchange, Ministry of Agriculture, The Superintendence of Stock Market, etc. Likewise, Damodarán website has been used, which allows to obtain financial variables from the international market that have allowed to apply the evaluation of discount rates. Among the studies carried out they have been applied the Horizontal and Vertical Analysis of the financial statements, the measurement and evaluation of the Financial Indicators of the company, Risk Analysis, Evaluation of internal and external factors - SWOT and PESTEL. Finally, based on the previously estimated analysis, conclusions and recommendations have been estimated, based on the impact on the application of IFRS on the company, being of great importance for a better decision making regarding the option of alienation of the corporate group.